Pola Adaptasi Sosial dan Komunikasi Pendatang Dengan Masyarakat Lokal - Samian Hadisaputra; Fatmawati (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2023)
Adaptation is a way that is done by each individual or group to get to know and be able to survive in their environment, this can be done with social interaction where one of the requirements of social interaction is communication. In this study the authors used a descriptive-qualitative method in which the researcher wanted to describe the social adaptations carried out by migrants and local communities in Bumijaya Village. Data collection techniques used are observation, interviews, and documentation. As for the results of the research that the authors did, namely: 1) Adaptation carried out by newcomers in the form of social interaction including through acculturation stages followed by assimilation, associative social interactions also occur, as well as formal and informal interactions which in interacting use primary communication processes. 2) Forms of communication used between migrants and local communities are verbal and nonverbal communication. Where in verbal communication there is a uniqueness in the use of the Javanese language which is similar between Jaa Serang and Central Java or East Java by immigrants from Central Java and East Java.